Study of Linguistics Aspect in Translation of English Education Department - Lihawa, Kartin; Pakaja, Marina; Napu, Novriyanto; Bouti, Suleman (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates linguistic aspects in the translation process carried out by English Education Department students at IAIN Sultan Amai Gorontalo. The research focuses on identifying common linguistic errors, analyzing their causes, and evaluating the linguistic competencies necessary for accurate translation. Conducted from April 4th to May 7th, 2024, the study utilized a mixed-methods approach, combining qualitative analysis of students’ translations of Factfulness by Hans Rosling, in-depth interviews, and classroom observations. AI tools assessed translation accuracy, while triangulation ensured data validity by comparing data sources and consulting experts. The findings highlight linguistic and cultural errors. Linguistic errors are categorized into morphology (58 errors), syntax (78 errors), and semantics (121 errors). Morphological errors stem from issues like singular-plural translation and affixation, while syntactic errors involve difficulties in adapting language structures. Semantic errors, the most prevalent, indicate challenges in conveying nuanced meanings accurately. Cultural errors (28 instances) are linked to students' limited understanding of cultural references, particularly those involving material culture and social organization. These results underscore the need to enhance students' linguistic and extralinguistic competencies. Recommendations include revising the curriculum to integrate cultural elements, fostering a deeper understanding of linguistic structures, and using innovative teaching strategies. This study provides insights into the linguistic challenges faced by students and offers practical suggestions to improve translation teaching, thereby contributing to better translation outcomes and more effective language education.